Synbiotic supplementation attenuates the promoting effect of indole-3-carbinol on colon tumorigenesis - De Moura, N. A. [UNESP]; Caetano, B. F.R. [UNESP]; Bidinotto, L. T. [UNESP]; Rodrigues, M. A.M. [UNESP]; Barbisan, L. F. [UNESP] (Brill Academic Publishers, 2021)
Indole-3 carbinol (I3C) has shown dual effects on the promotion and progression stages of colon carcinogenesis while synbiotics (Syn) have exerted anti-carcinogenic activities in most rodent studies. This study aimed to investigate the effects of I3C given alone or together with a Syn intervention on 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis. All animals were given four subcutaneous DMH injections (4×40 mg/kg bodyweight, twice a week for two weeks) and then received either basal diet (G1), basal diet containing I3C (1g/kg chow) (G2) or basal diet containing I3C+Syn (I3C + inulin 50g/kg chow + Bifidobacterium lactis BB-12®), 2.5×1010 cfu/g of basal diet), (G3) for 21 weeks. Dietary I3C (G2) significantly increased tumour volume and cell proliferation when compared to the DMH control group (G1). Syn intervention (G3) significantly reduced tumour volume and cell proliferation when compared to I3C (G2). The colon tumours found were classified into well-differentiated tubular adenomas or adenocarcinomas. Dietary I3C or I3C+Syn did not significantly affect the incidence and the multiplicity of tumours in comparison with the DMH control group. Furthermore, Syn intervention (G3) increased Gstm1 and reduced Mapk9 gene expression in colonic tumours. The findings of the present study show that the dietary I3C shows a weak promoting activity, while the combination with Syn ameliorates I3C effects.
Keywords: 1,2-dimethylhydrazine; Bifidobacterium lactis BB-12; Colon carcinogenesis; Colorectal cancer